2021
DOI: 10.3390/cancers13081987
|View full text |Cite
|
Sign up to set email alerts
|

Down-Regulation of the Proteoglycan Decorin Fills in the Tumor-Promoting Phenotype of Ionizing Radiation-Induced Senescent Human Breast Stromal Fibroblasts

Abstract: Down-regulation of the small leucine-rich proteoglycan decorin in the stroma is considered a poor prognostic factor for breast cancer progression. Ionizing radiation, an established treatment for breast cancer, provokes the premature senescence of the adjacent to the tumor stromal fibroblasts. Here, we showed that senescent human breast stromal fibroblasts are characterized by the down-regulation of decorin at the mRNA and protein level, as well as by its decreased deposition in the pericellular extracellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 117 publications
(93 reference statements)
0
19
0
Order By: Relevance
“…The lack of decorin in various mouse models of mesenchymal and epithelial neoplasms is permissive for tumorigenesis [61][62][63]; conversely, decorin can suppress tumorigenesis, invasion, and metastasis of inflammatory breast cancer [64]. This is further underscored by a recent study demonstrating that decorin is downregulated in senescent fibroblasts, which additively drives the tumor-promoting phenotype of ionizing radiation induced premature senescence [65]. Decorin may also serve as an important diagnostic biomarker for patients with advanced stage (II or III) breast cancer as it emerged as an independent predictive factor for these stages [66].…”
Section: Decorin Is the Prototypical Heterobifunctional Small Leucine...mentioning
confidence: 99%
“…The lack of decorin in various mouse models of mesenchymal and epithelial neoplasms is permissive for tumorigenesis [61][62][63]; conversely, decorin can suppress tumorigenesis, invasion, and metastasis of inflammatory breast cancer [64]. This is further underscored by a recent study demonstrating that decorin is downregulated in senescent fibroblasts, which additively drives the tumor-promoting phenotype of ionizing radiation induced premature senescence [65]. Decorin may also serve as an important diagnostic biomarker for patients with advanced stage (II or III) breast cancer as it emerged as an independent predictive factor for these stages [66].…”
Section: Decorin Is the Prototypical Heterobifunctional Small Leucine...mentioning
confidence: 99%
“…Chemotherapy and ionizing radiation are genotoxic for cancer cells, leading them to cell cycle arrest or apoptosis 13 . However, several studies have shown that these DNA‐damaging anti‐cancer remedies also inevitably affect stromal cells, provoking their premature senescence 1,14–17 . Cellular senescence—first described in human embryonic lung fibroblasts 18 —could be the result of replicative exhaustion due to telomere attrition (known as replicative senescence) or arise after exposure of the cells to sub‐cytotoxic genotoxic stresses (the so‐called stress‐induced premature senescence, SIPS) 19–21 .…”
Section: Introductionmentioning
confidence: 99%
“…1,2,22 SASP is the main phenotypic trait of senescent cells that has been connected with observed tumor-promoting senescenceassociated alterations in the architecture of the microenvironment adjacent to the tumor. [15][16][17]23,24 Current literature has mainly focused on the role of senescent stromal fibroblasts in breast cancer progression, given that this is the key cell type which is responsible for the synthesis and deposition of ECM components and the secretion of paracrine mediators acting on cancer cells. [25][26][27][28] We have recently shown that ionizing radiation provokes the premature senescence of breast stromal fibroblasts in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mavrogonatou et al revealed that stromal senescence, as a side-effect of radiotherapy, results in the tumor-promoting phenotypic trait of ionizing radiation-induced prematurely senescent human stromal fibroblasts, which is correlated with the decreased deposition in the pericellular matrix of the SLRP, decorin. Senescence-associated decorin downregulation is mediated by bFGF and VEGF in an autocrine manner, while autophagy activation through mTOR inhibition enhanced decorin expression [ 23 ]. Finally, a compelling study in this Special Issue was conducted by Caon et al, who identified a novel target to induce HA synthase 2 (HAS2) in stromal fibroblasts.…”
mentioning
confidence: 99%